Studi Eksploratif: Pengungkapan Lingkungan pada Pelaporan Industri Fast Fashion - Jannati, Annisa Nur (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2024)
This exploratory study examines environmental disclosure practices in the fast-fashion industry, focusing on PT Matahari Department Store Tbk. The study employs a descriptive qualitative approach using secondary data obtained from the company’s annual reports, sustainability report, books, journals, and previous studies. Data were analyzed through document analysis, content analysis, and legitimacy analysis. Environmental disclosure was evaluated using themes covering environmental compliance, environmental costs and liabilities, future environmental cost estimates, legal proceedings, environmental policies, natural-resource conservation, emissions, waste, environmentally friendly technology, environmental awards, and environmental education. The results show that the company demonstrates a strong commitment to environmental responsibility through initiatives such as reducing plastic and paper consumption, managing waste responsibly, using environmentally friendly materials, integrating environmental considerations into operations, participating in collaborative activities, and receiving environmental recognition. These disclosures contribute to obtaining and maintaining corporate legitimacy. However, the company provides limited information concerning future environmental cost estimates and potential legal consequences related to environmental issues. Therefore, greater transparency in environmental financial and legal disclosures is recommended.